Development of a monoclonal antibody and a lateral-flow device for the rapid detection of a Mucorales-specific biomarker - Thornton, Christopher R.; Davies, Genna E.; Dougherty, Laura (Frontiers in Cellular and Infection Microbiology, 2023)
Mucoromycosis is a highly aggressive angio-invasive disease of humans caused by fungi in the zygomycete order, Mucorales. While Rhizopus arrhizus is the principal agent of mucoromycosis, other Mucorales fungi including Apophysomyces, Cunninghamella, Lichtheimia, Mucor, Rhizomucor and Syncephalastrum are able to cause life-threatening rhino-orbital-cerebral, pulmonary, gastro-intestinal and necrotising cutaneous infections in humans. Diagnosis of the disease currently relies on non-specific CT, lengthy and insensitive culture from invasive biopsy, and time-consuming histopathology of tissue samples. At present, there are no rapid antigen tests that detect Mucorales-specific biomarkers of infection, and which allow point-of-care diagnosis of mucoromycosis. Here, we report the development of an IgG2b monoclonal antibody (mAb), TG11, which binds to extracellular polysaccharide (EPS) antigens of between 20 kDa and 250 kDa secreted during hyphal growth of Mucorales fungi. The mAb is Mucorales-specific and does not cross-react with other yeasts and molds of clinical importance including Aspergillus, Candida, Cryptococcus, Fusarium, Lomentospora and Scedosporium species. Using the mAb, we have developed a Competitive lateral-flow device that allows rapid (30 min) detection of the EPS biomarker in human serum and bronchoalveolar lavage (BAL), with a limit of detection (LOD) in human serum of 100 ng/mL serum ( 224.7 pmol/L serum). The LFD therefore provides a potential novel opportunity for detection of mucoromycosis caused by different Mucorales species.